Comparative Evaluation of the Antimicrobial Activity of Different Antimicrobial Peptides against a Range of Pathogenic Bacteria. - Anna Ebbensgaard; Hanne Mordhorst; Michael Toft Overgaard; Claus Gyrup Nielsen; Frank Møller Aarestrup; Egon Bech Hansen (PLoS ONE)
Analysis of a selected set of antimicrobial peptides The rapid emergence of resistance to classical antibiotics has increased the interest in novel antimicrobial compounds. Antimicrobial peptides (AMPs) represent an attractive alternative to classical antibiotics and a number of different studies have reported antimicrobial activity data of various AMPs, but there is only limited comparative data available. The mode of action for many AMPs is largely unknown even though several models have suggested that the lipopolysaccharides (LPS) play a crucial role in the attraction and attachment of the AMP to the bacterial membrane in Gram-negative bacteria. We compared the potency of Cap18, Cap11, Cap11-1-18m2, Cecropin P1, Cecropin B, Bac2A, Bac2A-NH2, Sub5-NH2, Indolicidin, Melittin, Myxinidin, Myxinidin-NH2, Pyrrhocoricin, Apidaecin and Metalnikowin I towards Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, Escherichia coli, Aeromonas salmonicida, Listeria monocytogenes, Campylobacter jejuni, Flavobacterium psychrophilum, Salmonella typhimurium and Yersinia ruckeri by minimal inhibitory concentration (MIC) determinations. Additional characteristics such as cytotoxicity, thermo and protease stability were measured and compared among the different peptides. Further, the antimicrobial activity of a selection of cationic AMPs was investigated in various E. coli LPS mutants. Cap18 shows a high broad spectrum antimicrobial activity Of all the tested AMPs, Cap18 showed the most efficient antimicrobial activity, in particular against Gram-negative bacteria. In addition, Cap18 is highly thermostable and showed no cytotoxic effect in a hemolytic assay, measured at the concentration used. However, Cap18 is, as most of the tested AMPs, sensitive to proteolytic digestion in vitro. Thus, Cap18 is an excellent candidate for further development into practical use; however, modifications that should reduce the protease sensitivity would be needed. In addition, our findings from analyzing LPS mutant strains suggest that the core oligosaccharide of the LPS molecule is not essential for the antimicrobial activity of cationic AMPs, but in fact has a protective role against AMPs.